Gastrointestinal motility during sleep assessed by tracking of telemetric capsules combined with polysomnography - a pilot study - Haase, Anne; Fallet, Sibylle; Otto, Marit; Scott, Mark S; Schlageter, Vincent; Krogh, Klaus (Clinical and experimental gastroenterology, 2015)
Studies of gastrointestinal function during sleep are hampered by lack of applicable techniques. Recent development of a novel ambulatory telemetric capsule system, which can be used in conjunction with polysomnography, offers a solution to this problem. The 3D-Transit system consists of ingestible electromagnetic capsules traceable through a portable extracorporeal receiver while traversing the gut. During sleep monitored by polysomnography, gastrointestinal motility was concurrently investigated using 3D-Transit in nine healthy subjects. Overall, the amplitude of gastric contractions decreased with depth of sleep (light sleep, N2 versus deep sleep, N3; P<0.05). Progression through the small intestine did not change with depth of sleep (Kruskal-Wallis probability =0.1), and there was no association between nocturnal awakenings or arousals and the occurrence of colonic or small intestinal propagating movements. Basal colonic activity was suppressed during both deep sleep (P<0.05) and light sleep (P<0.05) when compared with nocturnal wake periods. In conclusion, the novel ambulatory 3D-Transit system combined with polysomnography allows minimally invasive and completely ambulatory investigation of associations between sleep patterns and gastrointestinal motility.